GRA-FAHP Model for Supplier selection in a Nickel Plating Industry: A Hybrid MCDM Approach - Sanatan Ratnac, Akhil Saji Abraham, Rudra Airi (International Journal of Advanced Science and Technology, 2019)
In the recent past, government of India has put lot of focus on its new policy i.e., “Make in India”, as a result of which, the Indian manufacturing sector has been looking forward to be on the cusps of being the manufacturing hub on the globe. As a result of this, the manufacturing firms are looking for suppliers with high level of efficiency and better quality. The problem arises when there is wide array of suppliers which are to be selected based on awide range of criteria. This leads to a multi criteria decision making problem i.e., MCDMproblem. Thesuppliers need to be ranked as per their efficiency based on a number of criteria and the best supplier needs to be chosen.The current research work deals with the selection best supplier for a Nickel plating industry using Grey relation analysis &Fuzzy AHP. The grey system theory was developed by Deng Julong of China in 1982.the concept of grey system is Arepresentation of an incomplete or uncertain information system as the grey color lies between black (no information) and white (all information).The method can convert a multiple response problem into a single response optimization problem by finding grey relation grades (GRG).Fuzzy AHP is different from AHP in the sense that it accommodates the imprecision and partial truth or rather the ambiguity in the input data. A hybrid of fuzzy logic with the conventional AHP becomes a much more effective MCDM tool to handle the subjective and linguistic inputs from the survey or feedback. FAHP makes use of a triplet of triangular fuzzy numbers (TFN) to include the ambiguity in the priorities during pairwise comparisons. Thecriteria under consideration for supplier selection are,Quality, Warranties& Claims Policies, Production Facilities and Capacity, Geographical Location of the supplier, Packaging Ability& FinancialPosition. Thesecriteria are given grey relation grades using GRA and the three most important criteria are shortlisted. In the next step, the suppliers are evaluated using Fuzzy AHP and the ranked accordingly. The supplier with the best rank is chosen in the Nickel plating industry. The proposed hybrid model can be useful in guiding the Indian Nickel plating industries and other SMEs in judicial selection of suppliers to gain significant advantages over the competitors. Keywords: GRA, AHP, Fuzzy AHP, MCDM problem, supplier selection, hybrid model.